New critical spaces in transitional justice : gender, art, and memory - Kurze, Arnaud; Lamont, Christopher K. (Indiana University Press, 2019)
Gathering work from contributors in international law, political science, sociology, and history, New Critical Spaces in Transitional Justice explains current trends in responses to post-conflict and post-authoritarian nations and offers original empirical research to help define the field for the future.
Keywords: Transitional justice.; Human rights.; Identity politics.; Justice transitionnelle.; Droits de l'homme (Droit international); Politique identitaire.; POLITICAL SCIENCE -- Political Freedom & Security -- Civil Rights.; POLITICAL SCIENCE -- Political Freedom & Security -- Human Rights.; Human rights; Identity politics; Transitional justice; Transitional Justice